2010
DOI: 10.1038/jhg.2010.84
|View full text |Cite
|
Sign up to set email alerts
|

A novel GATA6 mutation in patients with tetralogy of Fallot or atrial septal defect

Abstract: GATA6 is a member of the GATA family of transcription factors, and its expression and functions overlap with those of GATA4 during heart development. Mutations in GATA4 have been related to human congenital heart diseases (CHDs) in several studies, whereas mutations in GATA6 have only recently been reported in patients with persistent truncus arteriosus. Animal experiments have revealed critical roles for GATA6 in the development of the myocardium and cardiac morphogenesis, thereby highlighting the potential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
61
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 32 publications
4
61
0
1
Order By: Relevance
“…Biochemical analysis demonstrated that the GATA6 A178V mutant protein resulted in increased transactivation ability for cardiac genes compared with the wildtype. Our first report and subsequent reports by Maitra et al 4 and Lin et al 2 in this issue provide an approach for the etiology of nonsyndromic or 'multi-factorial' CHD in the post-genomic era, and together indicate that mutations in GATA6 cause CHD implicated in the cardiac OFT and septal development.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Biochemical analysis demonstrated that the GATA6 A178V mutant protein resulted in increased transactivation ability for cardiac genes compared with the wildtype. Our first report and subsequent reports by Maitra et al 4 and Lin et al 2 in this issue provide an approach for the etiology of nonsyndromic or 'multi-factorial' CHD in the post-genomic era, and together indicate that mutations in GATA6 cause CHD implicated in the cardiac OFT and septal development.…”
mentioning
confidence: 59%
“…2 The same mutation was also observed in their parents, two fathers with no CHD and a mother with bicuspid aortic valve. In previous reports, GATA4 missense mutations identified in patients with cardiac septal defects were also found in some of their non-affected parents or family members, indicating the reduced penetrance of the phenotype.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Emerging evidence underscores the crucial role for several transcription factors, including NKX2-5, GATA4 and GATA6, in the proper cardiogenesis (38)(39)(40) and mutations in these genes have been causally linked to congenital cardiovascular anomalies and AF (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). GATA5 is another member of the GATA family and its expression and function overlap with those of GATA4 and GATA6 during cardiac development, particularly in the regulation of target gene expression synergistically with NKX2-5 (57,58), suggesting the potential association of functionally compromised GATA5 with AF.…”
Section: Introductionmentioning
confidence: 99%
“…GATA6 gene mutations have been reported in familial and isolated CHD patients in different ethnic populations, including atrial septal defect, atrioventricular septal defect, persistent truncus arteriosus, tetralogy of Fallot and ventricular septal defect (VSD) [16][17][18][19][20][21][22][23][24][25]. Mutations in GATA6 gene include missense mutations, deletions and copy number variants.…”
Section: Introductionmentioning
confidence: 99%